Identification Of Causes Of Damage In Lathe Using FMEA (Failure Mode And Effect Analysis) And RCA (Road Cause Analysis) Methods - Ghofur, M. Abdul; Andesta, Deny (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
PT. XYZ is a service company in the field of construction and fabrication. The purpose of this research is to identify critical components in system failure on the lathe unit, to find out how often a failure on the lathe is likely to occur, to find out the causes of damage to the lathe machine components and to be able to find out the criteria of risk that has the highest risk score and RPN. The analysis process in this study needs to be done to minimize damage to the lathe. If there is damage to the lathe, the production process cannot run smoothly. For the production process to run smoothly, it is necessary to have machine maintenance activities. Machine maintenance activities aim to keep machines in good condition and ready for use in the production process. The method used in this research is FMEA and RCA. The FMEA method can be used as a system to prevent errors that are predicted to occur. This method is carried out by sorting the RPN value from the highest and then suggesting improvements to the lathe. Meanwhile, the RCA method is a structured approach to identifying influencing factors in one or more past events so that it can be used to improve performance. There are various structured evaluation methods to identify the root causes of problems. The results of this study are the two most significant RPN values, namely the Chuck and Gear components. The cause of the failure of these components is for the chuck. When setting, the chuck is not a flashlight, while the machine is not functioning properly for the gear.